Die Geschichte des Finanzplatzes Hamburg: Anmerkungen aus Sicht einer Zentralbank - Arno Bäcker; Christian Hecker (IBF - Institut für Bank- und Finanzgeschichte, 2017)
– Two features of the history of Hamburg as a financial centre are of particular interest from the perspective of a central bank: The estab-lishment of Hamburger Bank in 1619 as a proto-central bank and the handling of two liquidity or financial crises in the 19th century. Hamburger Bank provided the regional economy with a stable unit of account by creating the Mark Banco. It was defined by a fixed amount of silver. Hamburger Bank took in deposits which were credited in Mark Banco. Therefore, the Mark Banco could also be used as an easy medium of exchange between creditors. As a result, de facto Hamburger Bank also served as a basic payment system. The stability of its unit of account and its settlement services made the bank attractive beyond local borders in supra-regional trade. It may well be argued that Hamburger Bank became a catalyst for the region's economic development. However, the bank did not have the means, nor did it have a public mission to help out in the financial crises which ensued following the big fire of Hamburg in 1842 and the international economic crisis of 1857. These events showed, inter alia, that liquidity and counterparty risks had been neglected by the mer-chant bankers of the day despite the backdrop of increased interna-tional trade and economic complexities. Furthermore, the resolution of the crisis of 1857 by public means was already viewed in a critical way by contemporaries who understood that such interventions could create future risks for the financial centre by means of moral hazard.
Keywords: G18; G21; N23; N24; 330